Comparison between anti‐VEGF therapy and corticosteroid or laser therapy for macular oedema secondary to retinal vein occlusion: A meta‐analysis. (22nd June 2017) - Qian, T.; Zhao, M.; Xu, X.
Summary: What is known and objective: Therapeutic effects of anti‐VEGF agents, corticosteroids and laser therapy have been previously examined for treating macular oedema secondary to branch and central retinal vein occlusion (BRVO and CRVO). However, anti‐VEGF efficacy has not been previously compared to corticosteroid or laser therapy efficacy. We performed a meta‐analysis to compare these treatments. Methods: Pertinent publications were identified through comprehensive literature searches. Therapeutic effects were estimated using best‐corrected visual acuity (BCVA), central retinal thickness (CRT) and intraocular pressure (IOP). The Review Manager (version 5.3.5) was used to perform searches. Results and discussion: Eleven randomized, controlled trials that included 1045 RVO patients were identified. For eyes with BRVO, anti‐VEGF therapy improved BCVA significantly more than corticosteroid/laser therapy at 3 ( P =.0002), 6 ( P <.00001) and 12 months ( P <.00001). For eyes with CRVO, this difference was only significant at 6 months ( P =.002). The same was true when efficacy was examined using CRT at 3 and 6 months (BRVO: both P <.00001, CRVO 6 months: P =.02). Long‐term efficacy of anti‐VEGF agents was limited in eyes with BRVO and CRVO. Improvements in BCVA were similar at 1 and 3 months ( P =.74), but BCVA decreased between 3 and 6 months ( P =.03). In contrast, BCVA progressively decreased 1 and 6 months following corticosteroid/laser therapy (both P <.00001). Lastly, eyes that had been treated with anti‐VEGF agents had significantly lower IOP changes than eyes treated with corticosteroids/laser 3 and 6 months after initiating therapy (both P <.00001). What is new and conclusion: Anti‐VEGF agents improve BCVA and reduce CRT more effectively and longer than corticosteroid/laser in eyes with RVO. Anti‐VEGF agents also have a lower risk of elevating IOP. Additionally, anti‐VEGF agents are more effective for treating BRVO than CRVO. Abstract : The meta‐analysis evaluates and compares the therapeutic effect of intravitreal anti‐VEGF agents and non‐anti‐VEGF therapeutic strategies for treating macular oedema secondary to retinal vein occlusion (RVO). The efficacy indicators include the mean changes in BCVA improvement and CRT reduction. Multiple time points are examined during the 12‐month period to evaluate how treatment efficacy changes over time. Changes in intraocular pressure (IOP) following treatment were also examined.